Biceps Femoris Long Head Muscle Fascicles Actively Lengthen During the Nordic Hamstring Exercise - Raiteri, Brent J.; Beller, Ronja; Hahn, Daniel (Frontiers in Sports and Active Living, 2021)
Current debate exists around whether a presumed eccentric exercise, the Nordic Hamstring Exercise (NHE), actually causes active hamstring muscle lengthening. This is because of the decoupling that can occur between the muscle fascicle and muscle-tendon unit (MTU) length changes in relatively compliant human lower-limb MTUs, which results in MTU lengthening not necessarily causing muscle fascicle lengthening. This missing knowledge complicates the interpretation of why the NHE is effective at reducing running-related hamstring muscle injury risk in athletes previously unfamiliar with performing this exercise. The purpose of the study was therefore to investigate if the most-commonly-injured hamstring muscle, the biceps femoris long head (BF), exhibits active muscle lengthening (i.e., an eccentric muscle action) during the NHE up until peak force in Nordic novices. External reaction forces at the ankle, knee flexion angles, and BF and semitendinosus muscle activities were recorded from the left leg of fourteen participants during the NHE. Simultaneously, BF muscle architecture was imaged using B-mode ultrasound imaging and muscle architecture changes were tracked using two different tracking algorithms. From ~85-100% of peak NHE force, both tracking algorithms showed that BF muscle fascicles (n = 10) significantly lengthened (p < 0.01) and had a mean positive velocity (p ≤ 0.02), while knee extension velocity remained positive (17°·s-1) over knee flexion angles from 53-37° and a duration of 1.6 s. Despite some individual cases of brief isometric fascicle behavior and brief muscle fascicle shortening during BF MTU lengthening, the predominant muscle action was eccentric under a relatively high muscle activity level (59% of maximum). Eccentric hamstring muscle action therefore does occur during the NHE in relatively strong (429 N) Nordic novices, which might contribute to the increase in resting BF muscle fascicle length and reduction in running-related injury risk that have previously been reported following NHE training. Whether an eccentric BF muscle action occurs in individuals accustomed to the NHE remains to be tested.